2004
DOI: 10.1128/mcb.24.21.9630-9645.2004
|View full text |Cite
|
Sign up to set email alerts
|

Human SWI/SNF-Associated PRMT5 Methylates Histone H3 Arginine 8 and Negatively Regulates Expression of ST7 and NM23 Tumor Suppressor Genes

Abstract: Protein arginine methyltransferases (PRMTs) have been implicated in transcriptional activation and repression, but their role in controlling cell growth and proliferation remains obscure. We have recently shown that PRMT5 can interact with flag-tagged BRG1-and hBRM-based hSWI/SNF chromatin remodelers and that both complexes can specifically methylate histones H3 and H4. Here we report that PRMT5 can be found in association with endogenous hSWI/SNF complexes, which can methylate H3 and H4 N-terminal tails, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
620
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 544 publications
(647 citation statements)
references
References 60 publications
22
620
3
2
Order By: Relevance
“…A number of experimental studies have shown that PRMT5 and H4R3me2 s repress gene expression [15-28]. In an experiment that is a direct analogue of our knockout analysis, silencing of PRMT5 in mouse cell lines resulted in more de-repressed than repressed genes in a microarray analysis [22], supporting our result that H4R3me2 s is globally repressive. PRMT5 is a member of the multi-subunit mSin3A and NuRD histone deacetylase complexes [26], suggesting H4R3me2 is associated with deacetylation and hence gene inactivation [22,23,26].…”
Section: Resultssupporting
confidence: 89%
“…A number of experimental studies have shown that PRMT5 and H4R3me2 s repress gene expression [15-28]. In an experiment that is a direct analogue of our knockout analysis, silencing of PRMT5 in mouse cell lines resulted in more de-repressed than repressed genes in a microarray analysis [22], supporting our result that H4R3me2 s is globally repressive. PRMT5 is a member of the multi-subunit mSin3A and NuRD histone deacetylase complexes [26], suggesting H4R3me2 is associated with deacetylation and hence gene inactivation [22,23,26].…”
Section: Resultssupporting
confidence: 89%
“…Previously we have shown that ST7 mutations are absent from primary breast cancers (Thomas et al, 2001) pointing to the downregulation of ST7 via epigenetic mechanisms. In pilot experiments, we have not detected significant hypermethylation of the ST7 gene promoter in primary breast cancers (unpublished observations) and it is likely that histone acetylation is the predominant mode of regulation of ST7 (Pal et al, 2004).…”
Section: Functional Characterization Of St7 Cs-f Hooi Et Almentioning
confidence: 87%
“…Interestingly, recent evidence suggests that histone methylation may be an important epigenetic modifier of ST7 transcription. The protein arginine methyltransferase 5 (PRMT5) can associate with the BRG1 chromatin remodeler to directly repress transcriptional activation of ST7 through regulating chromatin accessibility (Pal et al, 2004). Furthermore, exogenous expression of PRMT5 in NIH 3T3 cells induced cell transformation that was associated with a decrease in ST7 expression.…”
Section: Functional Characterization Of St7 Cs-f Hooi Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila the two forms of SWI/SNF called BAP (Brahma associated proteins) and PBAP (Polybromo-associated BAP) both contain the same catalytic subunit (Brahma), but are distinguished by BAP containing the OSA subunit and PBAF containing the Polybromo and BAP170 subunits [10]. Although human SWI/SNF can be characterized as being of two forms, namely BAF (BRG1/hBRM-Associated Factors) and PBAF (Polybromo-associated BAF), there are many forms of human SWI/SNF that acquire tissue-specific subunits [11] or additional sub-complexes in which the SWI/SNF-type remodelers are associated with other factors such as BRCA1 [12,13], components of the histone deacetylase Sin3 complex [14] and histone methylases [15,16]. Recently, Rtt102p was identified as the newest subunit of both SWI/SNF and RSC complexes by MudPIT or mass spectrometry analysis [17].…”
Section: Nucleosome Remodeling Complexes Swi/snf Familymentioning
confidence: 99%